A simple mathematical model of a single sculling technique - Wychowanski, M.; Slugocki, G.; Orzechowski, G.; Staniak, Z.; Radomski, D.; Trzcinski, A.; Wit, A. (ISBS Proceedings Archive (Michigan), 2017)
The results in sport in rowing depend on the two most important factors, such as the athlete physical features and the techniques of motion. The assessment and optimisation of rowing techniques are possible only when one disposes the reliable mathematical model predicting the results of the regatta that is the time of covering an assumed distance. A single scull participating in the 2000 meters distance regatta is our subject. The purpose of this study is to create a simplified mathematical model to simulate the rowing boat dynamics. The boat-rower system is treated as a material point here. The oar has a prescribed angular motion vs. oarlock depending on the time. The hydrodynamics force distribution to be developed on the oar`s blade has been modelled here. Then, the boat motion was described by a single nonlinear ordinary differential equation (NODE). The proposed simple model gives the possibilities of fast and reliable simulation of the single sculling technique and forecasts the result of rowing regattas.